Internet connectivity disruption in DR Congo (DR Congo) - Voidly (2026)
CRITICAL severity disruption detected in DR Congo. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: CD-2026-0036
Keywords: internet disruption; CD; disruption; critical